(untitled) (Research, Society and Development, 2020)
The fall armyworm, Spodoptera frugiperda, causes damage at several stages of the maize crop cycle. Due to its resistance to synthetic insecticides and the high costs of pest control, there is an ever-increasing amount of research on alternative or complementary products that have a minor environmental and financial impact on agriculture. Therefore, the aim of this study was to evaluate the chemical composition and insecticidal potential of Ocimum gratissimum (african basil) leaves essential oil and the effect of its major component, thymol, on S. frugiperda control. Gas Chromatography (GC) and Gas Chromatography-Mass Spectrometry (GC-MS) analysis identified p-cymene, γ-terpinene, and thymol compounds as the main constituents of the oil, which presented a yield of 4.75%. Among the 30 identified compounds, thymol (33.2%) was the major constituent, representing 97.8% of the total oil. The efficacy of both the oil and thymol standard (Sigma-Aldrich) was evaluated against S. frugiperda using topical acute toxicity and contact surface tests at different concentrations. The oil was more active than thymol standard, with topical acute toxicity of LD50 at 0.020 μl/insect and LC50 at 0.171 μl/cm2 for contact surface toxicity. The oil proved to be superior to the thymol standard, offering an effective and promising alternative for the control of S. frugiperda, which is most likely due to the contribution of other oil components that acted synergistically. Consequently, this result provides an opportunity for further study and the development of an effective fall armyworm control system.